(untitled) (Medicine Today, 2021)
Introduction: The epilepsy associated co morbidities are often underestimated, consequently, undertreated. The aim of the present study was to determine neurodevelopmental co morbidities associated with poorly controlled childhood epilepsy. Materials and Methods: This retrospective study was performed from January 2007 to December 2008 at Paediatric Neurology outpatient department in Bangabandhu Sheikh Mujib Medical University, Dhaka, among the children with epilepsy of 7 months to 15 years age who had history of at least 6 months treatment with rational antiepileptic drugs daily with adequate compliance. There were two groups of patients; group 1, consisted of 50 poorly controlled epilepsy patients and group 2, comprised 50 well-controlled epilepsy patients. We retrospectively reviewed EEGs and medical records from these children. Features of neurolodevelopmental co morbidities were compared between the two groups. Results: In this study, initial EEG was abnormal significantly in poorly controlled group (OR= 5.27; p=0.025). Co morbidities- cerebral palsy, language and speech delay, motor delay, microcephaly and cognitive disability were significantly higher in poorly-controlled epilepsy group compared to well-controlled epilepsy group (60.0% vs. 24.0%, p <0.001; 74.0% vs. 38%, p <0.001; 72% vs. 40%, p <0.01; 60% vs. 30.0%, p <0.01; 70% vs 32%, p <0.001 respectively). Conclusion: The study showed several neurodevelopment co morbidities that can be identified early in the course of childhood epilepsy which can predict development of poor seizure control. Knowledge of these co morbidities will help us to discriminate our patient and can inform therapeutic choices. Medicine Today 2021 Vol.33(1): 65-70